Pengaruh Persepsi Keadilan Pada Perilaku Konsumsi Berkelanjutan Dalam Perspektif Dilema Sosial - V. Rachmadi Parmono (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2013)
Environmental issues are social dilemmas. In a social dilemma, the individual is faced with the choice to put his personal interests, or cooperate with other individuals by prioritising the common interest. Researcher look at environmental problems has two interrelated issues, namely the issue of environmental justice and sustainable consumption issues. This research will investigate individual’s perceived justice on willingness to cooperate in social dilemma situation. Willingness to cooperate is representing sustainable consumption in social dilemma’s term. This study used experimental method. The results of this studies were as follows. Individual’s perceived justice is determined the willingness to cooperate. Over consumption behavior seemed create unfairness to individuals. Participants were prefer equity rules of fairness than equality rule of fairness to distribute resources among them. The awareness of social dilemma is having a role as a partial mediation that mediate the influence of perceived justice to willingness to cooperate. The awareness of social dilemma altered the preference of fairness from equity to equality.